DIVERSITY AND ABUNDANCE OF THE BEETLES IN DIFFERENT CROPS OF DISTRICT LAYYAH (Journal of Medical & Health Sciences Review, 2025)
Insects are the most dominant and diverse creatures on the earth. The Coleoptera order, to which beetles belong, is the most distinct order among insects, with 400,000 species described in 170 families. Not only do they prey on crop-damaging pests such as jassids, aphids and whiteflies, but they are also excellent decomposers. The coccinellidae beetles are recognized as being of great economic significance in agroecosystems. The present study was executed to estimate the diversity and abundance of beetles in different crops of district Layyah. Samples were collected fortnightly by using pit fall traps, sweep netting, optionally by hand-picking in the morning and afternoon from seasonal crops (wheat, maize and mustard) in covered glass vial jar then preserved in ethanol and brought to laboratory. The species richness of seven Coccinella septempunctata, E. indica, S. quadrillum, C. transversalis, H. axyridis, C. sexmaculata and P. vigintiduopunctata was measured. The diversity and abundance of coccinellidae species was recorded maximum in maize crop while at wheat crop was observed minimum. The diversity index of coccinellids species was recorded as (H0=1.7633), Evenness (0.904) and Dominance (0.8006) among the three crops of district Layyah. C. septempuntata was the most abundant species, accounting for 181 (34.54%) and least abundant species was S. quadrillum with 30 (5.72%) specimens. The obtained data and results were analyzed statistically by one-way ANOVA. Then p-value of all the f-ratio of six months for three crops was less than 0.001 which shows the highly significant results.